2023
DOI: 10.1002/leap.1558
|View full text |Cite
|
Sign up to set email alerts
|

Article processing charges for open access journal publishing: A review

Abstract: Some open access (OA) publishers charge authors fees to make their articles freely available online. This paper reviews literature on article processing charges (APCs) that has been published since 2000. Despite praise for diamond OA journals, which charge no fees, most OA articles are published by commercial publishers that charge APCs. Publishers fix APCs depending on the reputation assigned to journals by peers. Evidence shows a relationship between high impact metrics and higher, faster rising APCs.Authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 197 publications
(229 reference statements)
1
3
0
Order By: Relevance
“…It is estimated that roughly a third to almost 50% of published scientific research is available as open access [32]. These results are consistent with previous studies investigating researchers in various disciplines such as social sciences and humanities, engineering, and natural sciences which found that participants were most knowledgeable about open access publishing [33][34][35][36].…”
Section: Plos Onesupporting
confidence: 89%
“…It is estimated that roughly a third to almost 50% of published scientific research is available as open access [32]. These results are consistent with previous studies investigating researchers in various disciplines such as social sciences and humanities, engineering, and natural sciences which found that participants were most knowledgeable about open access publishing [33][34][35][36].…”
Section: Plos Onesupporting
confidence: 89%
“…Time and effort into publications relating to waste are also a cost. Considering the approximately 15 000 publication published on food waste until 2022 and the average cost of article processing charges (APCs) for open access journals between 2800 and 3000 US$ (36% open access journals), regardless of the cost of generating data and writing those papers on food waste, 47 substantial additional costs of food waste have been accumulated.…”
Section: Food Wastage: Statistics and Impactsmentioning
confidence: 99%
“…These constraints limit access to publication avenues, resulting in valuable research remaining unpublished or inaccessible. Consequently, knowledge sharing is stifled and the pace of scientific inquiry is impeded, perpetuating inequalities in academia (Borrego, 2023;Budzinski et al, 2020;Siler and Frenken, 2020). These challenges significantly impede the publication process and the dissemination of credible research within the academic community.…”
Section: Challenges In Scholarly Publishingmentioning
confidence: 99%